Evidence-based science activities in grades 3-5 : meeting the NGSS - Brown, Patrick, 1978-; Concannon, James (New York : Routledge, 2019)
"This new book shows elementary teachers how evidence-based science activities help students achieve deeper conceptual understanding. Drawing on a wealth of research, authors Pat Brown and Jim Concannon demonstrate how direct, hands-on experience in the science classroom can enable your students to become more self-reliant learners. They also provide a plethora of model lessons aligned with the Next Generation Science Standards (NGSS) and offer advice on how to create your lesson plans and activities to satisfy the demands of your curriculum. With the resources in this book, you and your students will be able to ditch the textbook and embark upon an exciting and rewarding journey to scientific discovery"--
Includes bibliographical references.
Keywords: Science -- Study and teaching (Elementary) -- United States; Inquiry-based learning -- United States; Next Generation Science Standards (Education)